2008
DOI: 10.1186/1471-213x-8-37
|View full text |Cite
|
Sign up to set email alerts
|

The RGS gene loco is essential for male reproductive system differentiation in Drosophila melanogaster

Abstract: BackgroundThe loco gene encodes several different isoforms of a regulator of G-protein signalling. These different isoforms of LOCO are part of a pathway enabling cells to respond to external signals. LOCO is known to be required at various developmental stages including neuroblast division, glial cell formation and oogenesis. Less is known about LOCO and its involvement in male development therefore to gain further insight into the role of LOCO in development we carried out a genetic screen and analysed males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…As it was reported that reduced fertility extends the lifespan of fruit flies (Partridge & Farquhar, 1981; Fowler & Partridge, 1989), we measured fertility of wild‐type and loco P283 heterozygous flies. The fertility, calculated as adult/egg number, was similar in both types (data not shown), consistent with a previous report showing that heterozygous loss of loco did not affect fertility (McGurk et al. , 2008).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As it was reported that reduced fertility extends the lifespan of fruit flies (Partridge & Farquhar, 1981; Fowler & Partridge, 1989), we measured fertility of wild‐type and loco P283 heterozygous flies. The fertility, calculated as adult/egg number, was similar in both types (data not shown), consistent with a previous report showing that heterozygous loss of loco did not affect fertility (McGurk et al. , 2008).…”
Section: Resultssupporting
confidence: 91%
“…, 2005; Kaplow et al. , 2008; McGurk et al. , 2008), a fine‐tuning of loco gene expression will be critical for the regulation of longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that Loco is required at various developmental stages, including as neuroblast division, glial differentiation, blood-brain barrier formation and reproductive systems, 14,15,17,[29][30][31] the changes of loco expression during embryonic development may cause detrimental consequences, such as lethality of loco homozygous mutant flies. 17,31 Future studies that investigate adult-specific regulation of loco expression will reveal more levels are reduced.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…17,31 Future studies that investigate adult-specific regulation of loco expression will reveal more levels are reduced. An alternative potential mechanism by which Loco inhibits Ras•GTP is to convert Ras•GTP into Ras•GDP by the GAP activity mediated through the RGS domain, as similarly occurs in the regulation of inhibitory Gαi•GTP protein.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…The WRC is composed of five proteins in C. elegans : WVE-1, GEX-2, GEX-3, ABI-1 and NUO-3. Soto et al (2002) [17] and Patel et al (2008) [18] presented evidence that suggested that GEX-2 and WVE-1, respectively, promote engulfment. Our genetic analysis, however, demonstrated that the CED-10 Rac pathway and ABI-1 act at least partially independently of each other.…”
Section: Introductionmentioning
confidence: 99%